(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research includes (an exploratory study of economic units in Iraq after the year 2003). The aims of our study can be clarified through the following questions: First: Does the exercise of the supervisory role in the economic unit require an important and essential role for the auditor based on the transformational leadership and self-marketing component. Second: Exercising the supervisory role in the economic unit requires adopting the arts of self-marketing for the accounts auditor to convey the content of his ideas and his method of work. Third: Does the application of international standards require the auditor’s involvement in a transformative leadership role, in order to reduce tensions and differences of opinion regarding the application of the mentioned standards. Fourth: Do workers in the various departments of the economic unit and mainly in the accounting departments need to be directed and led towards the new reality of applying international standards, or not.